Penyusunan Sistem Perencanaan Karier Pemerintah Kabupaten Klaten, Jawa Tengah - WINARSIH, ATIK SEPTI; RATMINTO, RATMINTO (Universitas Muhammadiyah Yogyakarta, 2011)
In any organization, institution or any institution would be expected an increase in career path foreach employee or employees who are on it. Career development and promotion is not based oncompetence and performance but rather on the DUK (Listings Sort ranks) and even sometimes basedon nepotism. Career civil servants who do not clear their determination is not supported and otherfactors that deserve consideration in determining an employee's career, the PNS will automaticallymove up and studied them on a regular basis every two years and received regular salary increases.Data collection methods used in this study were: 1) Observations and interviews conducted in each ofthe personnel involved in the activities of Employee Career Planning System, 2) Study of literatureintended to get a design plan based on the theory that there is a career in Human ResourceManagement; 3) Focus Group Discussion (FGD). The results obtained in this study that the civilservant career planning system that fits the context and needs of Klaten is oriented on the competenceof employees. Career planning system was developed under the provisions of current legislation.